Flocking-imitating PC plastic material as well as preparation method and application thereof
By selecting PC resins with different melting indexes in PC materials, combining black pigments and fiber dots, the problem of difficult to achieve high blackness and high fiber dots in automotive interior applications in the prior art is solved, and an efficient imitation flocking aesthetic effect is achieved.
Patent Information
- Application Number
- CN202510022417.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-07
AI Technical Summary
It is difficult to achieve the imitation flocking aesthetic effect of high blackness, no tailing phenomenon and high fiber point emergence rate in automotive interior applications.
By selecting two PC resins with different melting indexes to match, combining black pigment and fiber dots, adjusting the flowability of resin and fiber dots during processing, reducing the embedding of fiber dots by black resin, and improving the emergence rate of fiber dots.
PC plastic materials with high blackness, no tailing phenomenon and high fiber point emergence rate are achieved, and are suitable for automotive interior and exterior decoration, home appliances and consumer electronics fields.
Smart Images

Figure CN119752146A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a flocking-like PC plastic material and a preparation method and application thereof. Background Art
[0002] Polycarbonate, also known as PC plastic, has excellent heat resistance, electrical insulation and processing performance, and is often used in the fields of body panels, instrument panels, etc. At the same time, plastic parts with spotted aesthetic effects are gradually gaining attention in the automotive interior and exterior decoration, home appliances and consumer electronics industries due to their integrated molding characteristics, and have formed a green and low-carbon trend.
[0003] For example, CN113861561A discloses a flocking-like polypropylene composite material and its preparation method and application. The invention focuses on the flocking-like aesthetic effect, antibacterial and anti-bacterial, and odor and dust removal functional display of the polypropylene composite material. For another example, CN117183202A discloses a polypropylene elastomer flocking-like plastic part and its preparation method. The invention mainly focuses on studying the influence of injection molding process on the flocking-like effect of polypropylene elastomer.
[0004] In summary, it can be seen that preparing PC materials with speckled aesthetic effects and applying them to the field of automotive interior decoration can not only respond to the green and low-carbon environmental protection theme, but also enrich the appearance of the products, thereby improving the recognition and value of the products; however, no relevant reports have been found so far, and because PC materials will add components with poor compatibility with PC, such as impact agents, to the material system to improve the material performance, the brightness of its color is much higher than that of the raw materials of a single PC resin. At the same time, the color of automotive interior materials is mainly dark black. Therefore, when the PC system is selected for automotive interior materials, compared with other resin systems, more carbon black powder needs to be added at the same blackness, but too much carbon black powder will seriously cover the speckled effect, affecting the widespread application of PC materials with speckled aesthetic effects.
[0005] Therefore, developing a flocking-like PC plastic material with high blackness, no tailing phenomenon and high fiber point emergence rate is still a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a flocking-like PC plastic material and a preparation method and application thereof. The flocking-like PC plastic material is obtained by selecting two PC resins with different melt indexes to obtain a PC plastic material with high blackness, no tailing phenomenon and high fiber point emergence rate. The PC plastic material can be widely used in the fields of automotive interior and exterior decoration, home appliances and consumer electronics.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a flocking-like PC plastic material, wherein the flocking-like PC plastic material comprises the following components in parts by weight:
[0009] 50-70 parts by weight of PC resin;
[0010] ABS resin 0-30 parts by weight;
[0011] Anti-impact agent 0-20 parts by weight;
[0012] Black pigment 0.1-1 parts by weight;
[0013] Fiber point 0.1-1 weight part;
[0014] The PC resin includes a first PC resin and a second PC resin, and the melt index of the first PC resin at 300° C. and 1.2 kg is ≤23 g / 10 min (e.g., 23 g / 10 min, 22 g / 10 min, 20 g / 10 min, 18 g / 10 min, 16 g / 10 min, 14 g / 10 min, 12 g / 10 min, 10 g / 10 min, 8 g / 10 min, 6 g / 10 min, 4 g / 10 min or 2 g / 10 min, etc.), and the melt index of the second PC resin at 300° C. and 1.2 kg is ≥25 g / 10 min in (for example, 26g / 10min, 28g / 10min, 30g / 10min, 32g / 10min, 34g / 10min, 36g / 10min, 38g / 10min, 40g / 10min, 42g / 10min, 44g / 10min, 46g / 10min, 48g / 10min, 50g / 10min, 52g / 10min, 54g / 10min, 56g / 10min, 58g / 10min, 60g / 10min, 70g / 10min, 80g / 10min or 100g / 10min, etc.).
[0015] The flocking-like PC plastic material provided by the present invention comprises PC resin, ABS resin, impact-resistant agent, black pigment and fiber dots, and the PC resin comprises a first PC resin and a second PC resin, and the melting index of the first PC resin under the conditions of 300°C and 1.2kg is ≤23g / 10min, and the melting index of the second PC resin under the conditions of 300°C and 1.2kg is ≥25g / 10min; on the one hand, by adding black pigment, the obtained flocking-like PC / ABS plastic material has the characteristic of high blackness; on the other hand, by limiting the PC resin to include a relative melting index of The combination of the two PC resins with different melt indexes, namely, a first PC resin with a lower melt index and a second PC resin with a relatively high melt index, effectively adjusts the fluidity of the black resin and the fiber points during processing, minimizes the flow rate difference between the two, and ensures that the cooling moment of the fiber points during processing can be synchronized with the solidification moment of the black resin, thereby reducing or even avoiding the embedding of the fiber points by the black resin, increasing the emergence rate of the fiber points in the black resin, and reducing the tailing phenomenon, ultimately obtaining a PC / ABS plastic material with high blackness (depth), no tailing phenomenon and high fiber point emergence rate.
[0016] Among them, the content of the PC resin can be 50 parts by weight, 52 parts by weight, 54 parts by weight, 56 parts by weight, 58 parts by weight, 60 parts by weight, 62 parts by weight, 64 parts by weight, 66 parts by weight, 68 parts by weight or 70 parts by weight, etc.; and the mass percentage of PC resin in the flocking-like PC plastic material is not less than 50%.
[0017] In the present invention, the PC resin includes aromatic polycarbonate, such as bisphenol A type PC resin.
[0018] The content of the ABS resin can be 0 parts by weight, 2 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight or 30 parts by weight, etc.
[0019] The content of the anti-impact agent can be 0 parts by weight, 2 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight or 20 parts by weight, etc.
[0020] The content of the black pigment can be 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight or 1 part by weight, etc.; and the mass percentage of the black pigment in the flocking-like PC plastic material is not less than 0.2%.
[0021] The content of the fiber dots may be 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight or 1 part by weight, etc.
[0022] Preferably, the melt index of the first PC resin at 300° C. and 1.2 kg is 8 to 18 g / 10 min.
[0023] Preferably, the melt index of the second PC resin at 300° C. and 1.2 kg is 28 to 60 g / 10 min.
[0024] In the present invention, the test method of the melt index of the first PC resin and the second PC resin can refer to ISO1133-1:2022.
[0025] Preferably, the mass ratio of the first PC resin to the second PC resin is 1:(1-5), for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:4, 1:4.5 or 1:5, and more preferably 1:(2.5-3.5).
[0026] Preferably, the L value of the flocking-like PC plastic material is ≤30, such as 30, 28, 26, 24, 22, 20, 18, 16, 14, 12 or 10, and more preferably ≤29.
[0027] In the present invention, the test method of the L value of the flocking-like PC plastic material can refer to GB / T3979-2008.
[0028] Preferably, the content of ABS resin in the flocking-like PC plastic material is 10 to 30 parts by weight.
[0029] Preferably, the melt index of the ABS resin at 220° C. and 10 kg is 5 to 80 g / 10 min, for example, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 17 g / 10 min, 19 g / 10 min, 21 g / 10 min, 23 g / 10 min, 25 g / 10 min, 30 g / 10 min, 50 g / 10 min, 70 g / 10 min or 80 g / 10 min, and more preferably 15 to 25 g / 10 min.
[0030] In the present invention, the test method for the melt index of the ABS resin may refer to ISO 1133-1:2022.
[0031] Preferably, the content of the anti-impact agent in the flocking-like PC plastic material is 10 to 20 parts by weight.
[0032] In the present invention, there is no particular limitation on the specific type of the anti-impact agent, and any anti-impact agent commonly used in the art can be selected.
[0033] For example, the impact-resistant agent may be selected from acrylates, acrylate-butadiene copolymers, and terpolymers of methyl methacrylate-butadiene-styrene.
[0034] Preferably, the black pigment includes any one of carbon black, perylene black or benzidine black, or a combination of at least two thereof, and more preferably carbon black.
[0035] Preferably, the fiber dots include mica flake-type fiber dots and / or glitter powder-type fiber dots.
[0036] Preferably, the flocking-like PC plastic material further includes any one of a heat-resistant agent, an antioxidant, a lubricant or a light stabilizer, or a combination of at least two thereof.
[0037] Preferably, the content of the heat-resistant agent in the flocking-like PC plastic material is less than 10 parts by weight, for example, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, 2 parts by weight or 1 part by weight.
[0038] In the present invention, there is no particular limitation on the specific type of the heat-resistant agent, and any heat-resistant agent commonly used in the art can be selected.
[0039] For example, the heat-resistant agent may be a random copolymer of styrene, nitrogen phenyl maleimide and maleic anhydride.
[0040] Preferably, the content of antioxidant in the flocking-like PC plastic material is 0.1-0.5 parts by weight, for example, 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight or 0.5 parts by weight.
[0041] Preferably, the antioxidant comprises a combination of a hindered phenol antioxidant and a phosphite antioxidant.
[0042] Illustratively, the hindered phenol antioxidants include 2,6-di-tert-butyl-4-methylphenol, antioxidant 1010, antioxidant 1076, and the like; the phosphite antioxidants include antioxidant 168, antioxidant 626, and the like.
[0043] Preferably, the content of lubricant in the flocking-like PC plastic material is 0.2-0.5 parts by weight, for example, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight or 0.5 parts by weight.
[0044] In the present invention, there is no particular limitation on the specific type of the lubricant, and any lubricant commonly used in the art may be selected.
[0045] Exemplarily, the lubricant includes a pentaerythritol lubricant, for example, pentaerythritol stearate.
[0046] Preferably, the content of light stabilizer in the flocking-like PC plastic material is 0.5-1 part by weight, for example, 0.5 part by weight, 0.55 part by weight, 0.6 part by weight, 0.65 part by weight, 0.7 part by weight, 0.75 part by weight, 0.8 part by weight, 0.85 part by weight, 0.9 part by weight, 0.95 part by weight or 1 part by weight.
[0047] In the present invention, there is no particular limitation on the specific type of the light stabilizer, and any light stabilizer commonly used in the art can be selected.
[0048] Exemplarily, the light stabilizer may be selected from UV-72, UV-234, and the like.
[0049] In a second aspect, the present invention provides a method for preparing the flocking-like PC plastic material as described in the first aspect, the preparation method comprising the following steps:
[0050] (1) mixing PC resin, ABS resin, black pigment, impact resist, optionally heat resist, optionally antioxidant, optionally lubricant and optionally light stabilizer to obtain a mixed material;
[0051] (2) The mixed material obtained in step (1) is mainly fed and the fiber point is side fed, and an extruder is used to extrude and mold the mixed material to obtain the flocking-like PC plastic material.
[0052] Preferably, the mixing time in step (1) is 3 to 5 min, for example, 3 min, 3.2 min, 3.4 min, 3.6 min, 3.8 min, 4 min, 4.2 min, 4.4 min, 4.6 min, 4.8 min or 5 min, etc.
[0053] Preferably, the extruder in step (2) is a twin-screw extruder.
[0054] Preferably, the extrusion molding temperature in step (2) is 240-250°C, for example, 240°C, 241°C, 242°C, 243°C, 244°C, 245°C, 246°C, 247°C, 248°C, 249°C or 250°C, etc.
[0055] In a third aspect, the present invention provides a use of the flocking-like PC plastic material as described in the first aspect in automobile interior and exterior decoration, consumer electronic appearance parts or household appliance appearance parts.
[0056] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] The flocking-like PC plastic material provided by the present invention comprises PC resin, ABS resin, impact-resistant agent, black pigment and fiber dots, wherein the PC resin comprises a first PC resin and a second PC resin, and the melting index of the first PC resin under the conditions of 300° C. and 1.2 kg is ≤23 g / 10 min, and the melting index of the second PC resin under the conditions of 300° C. and 1.2 kg is ≥25 g / 10 min; by selecting the above two PC resins with different melting indexes for matching, the embedding of the fiber dots by the black resin is effectively reduced, the emergence rate of the fiber dots in the black resin is increased, and the tailing phenomenon is also reduced, and finally a PC plastic material with high blackness, no tailing phenomenon and high fiber dot emergence rate is obtained, which is very suitable for application in the fields of automotive interior and exterior decoration, home appliances and consumer electronics. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a physical picture of the flocking-like PC plastic material provided in Example 1;
[0060] Figure 2 This is a physical picture of the flocking-like PC plastic material provided in Comparative Example 1;
[0061] Figure 3 This is a physical picture of the flocking-like PC plastic material provided in Comparative Example 5. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0063] The information of some raw materials involved in the following examples and comparative examples is as follows:
[0064] (A) PC resin
[0065] PC resin 1A: melt index is 10g / 10min (300℃ / 1.2kg), purchased from Luxi Chemical Industry, brand name TY1609T-11;
[0066] PC resin 1B: melt index is 15 g / 10 min (300°C / 1.2 kg), purchased from Saudi Basic Industries Corporation, brand name PC FXE4271L;
[0067] PC resin 1C: melt index is 22 g / 10 min (300 ° C / 1.2 kg), purchased from Saudi Basic Industries Corporation, brand name PC HP2EU;
[0068] PC resin 1D: melt index is 5g / 10min (300℃ / 1.2kg), purchased from SABIC, brand name is LEXAN TM PC0700.
[0069] PC resin 2A: melt index is 30g / 10min (300℃ / 1.2kg), purchased from Mitsubishi Engineering, brand name is PCH-3000F;
[0070] PC resin 2B: melt index is 46 g / 10 min (300°C / 1.2 kg), purchased from Saudi Basic Industries Corporation, brand name PC XHT2146;
[0071] PC resin 2C: melt index is 26g / 10min (300℃ / 1.2kg), purchased from Formosa Chemical Corporation, brand name is PCIR1700;
[0072] PC resin 2D: melt index is 71 g / 10 min (300°C / 1.2 kg), Covestro, brand name is Makrolon DP 1-1265.
[0073] (B) ABS resin: melt index is 20 g / 10 min (220° C. / 10 kg), purchased from Liaoning Jinfa Technology Co., Ltd., brand ABS KF-730.
[0074] (C) Anti-impact agent: specifically, an acrylic anti-impact agent purchased from Anqiu Donghai Plastic Industry Co., Ltd., with a brand number of Q500.
[0075] (D) Black pigment
[0076] Carbon black: purchased from Cabot, brand M717;
[0077] Perylene black: purchased from BASF, brand name Black L 0086;
[0078] Benzidine black: purchased from Shanghai Tianrui Trading Co., Ltd., brand name Black R.
[0079] (E) Fiber point:
[0080] Mica fiber dots: purchased from Juhai Branch of Cangzhou Dahua Co., Ltd., brand number CH8115;
[0081] Glitter powder fiber dots: purchased from Changjin New Materials, brand number CLW01-128.
[0082] (F) Heat-resistant agent: specifically, a random copolymer of styrene, nitrogen phenyl maleimide and maleic anhydride, purchased from Jiaxing Huawen Chemical Co., Ltd., with the brand name HW-320.
[0083] (G) Antioxidants
[0084] Antioxidant 1076: hindered phenol antioxidant, purchased from Tianjin Li'anlong New Materials Co., Ltd., brand name RIANOX 1076;
[0085] Antioxidant 168: a phosphite antioxidant purchased from Tianjin Li'anlong New Materials Co., Ltd., with the brand name RIANOX 168.
[0086] (H) Lubricant: specifically pentaerythritol stearate, purchased from Shanghai Cheng Zai Cheng Chemical Co., Ltd., with the brand name PETS-AP.
[0087] (I) Light stabilizer: purchased from Suqian Liansheng Technology Co., Ltd., brand name UV-234.
[0088] Examples 1 to 15 and Comparative Examples 1 to 11
[0089] Examples 1 to 15 and Comparative Examples 1 to 11 respectively provide a flocking-like PC / ABS plastic material, and the components and amounts thereof are shown in Table 1 and Table 2;
[0090] In Tables 1 and 2, the dosage units of each component are "parts by weight";
[0091] Table 1
[0092]
[0093]
[0094] Table 2
[0095]
[0096]
[0097] The preparation method of the flocking-like PC / ABS plastic material provided in Examples 1 to 15 and Comparative Examples 1 to 12 comprises the following steps:
[0098] (1) PC resin, ABS resin, black pigment, impact resistant agent, heat resistant agent, antioxidant, lubricant and light stabilizer are mixed for 4 minutes to obtain a mixed material;
[0099] (2) The mixture obtained in step (1) is mainly fed and the fiber point is side fed, and extrusion molding is performed at 250° C. using a twin-screw extruder to obtain the flocking-like PC plastic material.
[0100] Appearance:
[0101] Visually observe the flocking-like PC plastic materials provided in Example 1, Comparative Example 1 and Comparative Example 5, and obtain the physical pictures of the flocking-like PC plastic materials provided in Example 1, Comparative Example 1 and Comparative Example 5, respectively. Figure 1 to Figure 3 As shown:
[0102] from Figure 1 to Figure 3 It can be seen from the comparison that the color plate fiber points obtained by injection molding the flocking-like PC plastic material provided in Example 1 emerge well and have no tailing phenomenon, which means that by selecting two PC resins with different melt indexes, the embedding of fiber points by black resin can be reduced or even avoided, the emergence rate of fiber points in black resin can be increased, and the tailing phenomenon can also be reduced.
[0103] Performance Testing:
[0104] (1) Lab value: The test was conducted using a Spectro 1050 desktop spectrophotometer in the reflectance mode in accordance with the test standard GB / T3979-2008 object color measurement method.
[0105] (2) Fiber point emergence rate: analyzed and tested using Leica microscope V2rayN;
[0106] Specific test method: first place the fiber spot under a microscope, take a photo with 6 times magnification, open the photo with IamgeJ software, and calculate the area S of a single fiber spot. 单个 ; Then place the imitation flocking PC / ABS plastic material color plate to be tested under a microscope, adjust the magnification to 6 times, take a photo of the imitation flocking PC / ABS plastic material color plate to be tested, open the photo with ImageJ software, and calculate the number of fiber points n and the total area S of the fiber points contained by the software. 总 The average area S of a single fiber point on the color plate of the PC / ABS plastic material to be tested is 浮现平均 =S 总 / n;
[0107] Fiber point emergence rate Sd (%) = 1 / n × SQRT [(S 浮现平均 -S 单个 ) 2 ]×100%;
[0108] (3) Tailing phenomenon: visual observation.
[0109] The flocking-like PC plastic materials provided in Examples 1 to 15 and Comparative Examples 1 to 12 were tested according to the above test method. The test results are shown in Table 3:
[0110] Table 3
[0111]
[0112]
[0113]
[0114] According to the data in Table 3, we can see that:
[0115] The flocking-like PC plastic materials provided in Examples 1 to 15 have both high blackness and high fiber point emergence rate, and have no tailing phenomenon; in particular, the flocking-like PC plastic materials provided in Examples 1 to 5 and Example 8 have an L value of 27.8 to 27.9, a fiber point emergence rate of up to 87 to 90%, a darker color and a higher fiber point emergence rate.
[0116] By comparing the data of Example 1 with Comparative Examples 1 to 8, it can be seen that since only the first PC resin or only the second PC resin is used, the flow rate difference between the resin and the fiber points is too large, which not only leads to a low fiber point emergence rate in the obtained PC plastic material, but also causes a tailing phenomenon due to the excessive flow rate difference.
[0117] By comparing the data of Example 1 with Comparative Examples 9-10, it can be seen that when the amount of black pigment added is too little (Comparative Example 9), the L value of the obtained PC plastic material is too high, the color of the PC plastic material is too light, and high blackness cannot be achieved; when the amount of black pigment added is too much (Comparative Example 10), the black pigment will be similar to a filler, hindering the flow of fiber points, resulting in poor emergence effect of the fiber points in the PC plastic material.
[0118] By comparing the data of Example 1 with Comparative Examples 11-12, it can be seen that the amount of fiber dots added also affects the emergence effect in the plastic material; when the amount of fiber dots added is small (Comparative Example 11), the emergence rate of fiber dots in the obtained PC plastic material is low; when the amount of fiber dots added is too large (Comparative Example 12), the fiber dots themselves are similar to fillers and have poor fluidity in the PC resin, which also leads to a poor emergence effect in the PC plastic material.
[0119] Further comparison of the data of Examples 1 to 3 with Examples 5 to 11 also shows that by further selecting a first PC resin and a second PC resin with a more suitable melt index for combination, the flow rate of the composite resin can be made closer to the flow rate of the fiber points, thereby enabling the fiber point emergence rate of the obtained PC plastic material to be higher.
[0120] By comparing the data of Examples 1 to 3 with those of Examples 12 to 13, it can be seen that in addition to the fact that the combination of the first PC resin and the second PC resin with suitable melt index will affect the emergence rate of the fiber points, the combination ratio of the first PC resin and the second PC resin will also affect the emergence rate of the fiber points. Only when the first PC resin and the second PC resin are combined in a suitable ratio can the obtained PC plastic material have a high fiber point emergence rate while having a high blackness.
[0121] Finally, by comparing the data of Example 1 with those of Examples 14 to 15, it can be seen that different types of black pigments will directly affect the L value, i.e., the depth value, of the obtained plastic material. Selecting perylene black and benzidine black as black pigments will result in a slightly higher L value of the obtained plastic material and a grayish color.
[0122] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A flocking-like PC plastic material, characterized in that: The flocking-like PC plastic material comprises the following components in parts by weight: 50-70 parts by weight of PC resin; ABS resin 0-30 parts by weight; Anti-impact agent 0-20 parts by weight; Black pigment 0.1-1 parts by weight; Fiber point 0.1-1 weight part; The PC resin includes a first PC resin and a second PC resin, and the melt index of the first PC resin at 300° C. and 1.2 kg is ≤23 g / 10 min, and the melt index of the second PC resin at 300° C. and 1.2 kg is ≥25 g / 10 min.
2. The flocking-like PC plastic material according to claim 1, characterized in that: The first PC resin has a melt index of 8 to 18 g / 10 min at 300° C. and 1.2 kg; Preferably, the melt index of the second PC resin at 300° C. and 1.2 kg is 28 to 60 g / 10 min; Preferably, the mass ratio of the first PC resin to the second PC resin is 1:(1-5), more preferably 1:(2.5-3.5).
3. The flocking-like PC plastic material according to claim 1 or 2, characterized in that: The L value of the flocking-like PC plastic material is ≤30, preferably ≤29.
4. The flocking-like PC plastic material according to any one of claims 1 to 3, characterized in that: The content of ABS resin in the flocking-like PC plastic material is 10 to 30 parts by weight; Preferably, the ABS resin has a melt index of 15 to 25 g / 10 min at 220° C. and 10 kg.
5. The flocking-like PC plastic material according to any one of claims 1 to 4, characterized in that: The black pigment includes any one of carbon black, perylene black or benzidine black or a combination of at least two thereof, and carbon black is more preferred; Preferably, the fiber dots include mica flake fiber dots and / or glitter powder fiber dots; Preferably, the content of the anti-impact agent in the flocking-like PC plastic material is 10 to 20 parts by weight.
6. The flocking-like PC plastic material according to any one of claims 1 to 5, characterized in that: The flocking-like PC plastic material further includes any one or a combination of at least two of a heat-resistant agent, an antioxidant, a lubricant or a light stabilizer; Preferably, the content of the heat-resistant agent in the flocking-like PC plastic material is less than 10 parts by weight; Preferably, the content of antioxidant in the flocking-like PC plastic material is 0.1 to 0.5 parts by weight; Preferably, the antioxidant comprises a combination of a hindered phenol antioxidant and a phosphite antioxidant; Preferably, the content of lubricant in the flocking-like PC plastic material is 0.2 to 0.5 parts by weight; Preferably, the content of the light stabilizer in the flocking-like PC plastic material is 0.5 to 1 part by weight.
7. A method for preparing the flocking-like PC plastic material according to any one of claims 1 to 6, the method comprising the following steps: (1) mixing PC resin, ABS resin, black pigment, impact resist, optionally heat resist, optionally antioxidant, optionally lubricant and optionally light stabilizer to obtain a mixed material; (2) The mixed material obtained in step (1) is mainly fed and the fiber point is side fed, and an extruder is used for extrusion molding to obtain the flocking-like PC plastic material.
8. The preparation method according to claim 7, characterized in that: The mixing time in step (1) is 3 to 5 minutes.
9. The preparation method according to claim 7 or 8, characterized in that: The extruder in step (2) is a twin-screw extruder; Preferably, the extrusion molding temperature in step (2) is 240-250°C.
10. Use of the flocking-like PC plastic material according to any one of claims 1 to 6 in automobile interior and exterior decoration, consumer electronic appearance parts or household appliance appearance parts.
Citation Information
Patent Citations
Flocking-imitating polypropylene composite material as well as preparation method and application thereof
CN113861561A
Flocking-imitating plastic part and preparation method thereof
CN117183202A
Low-gloss polypropylene composition with imitation flocking effect as well as preparation method and application of composition
CN104109287A
Preparation method of PC / ABS (Acrylonitrile Butadiene Styrene) functional master batch and composite materials thereof with faint scent smell and imitated flocking effect
CN109486160A
High-blackness PC / ABS alloy material for automotive upholstery and preparation method thereof
CN110982239A
Cited By
Flocking-imitating resin composition as well as preparation method and application thereof
CN121427244A
A suede forming mold and a suede plastic part having the same
CN224714325U